A Large Retinal Capillary Hemangioma in the Anterior Retina Treated with Photodynamic Therapy - Janice Cheung; Gary K.Y. Lee; Clement C.Y. Tham (Case Reports in Ophthalmology, 2012)
Purpose: To report a case of a large anterior retinal capillary hemangioma (RCH) treated successfully with photodynamic therapy (PDT). Methods: Case report. Results: A 12-mm-large RCH located in the anterior retina, with vision-threatening exudative complications that had not responded to cryotherapy and repeated laser photocoagulations, was treated with PDT using verteporfin. Exudation regressed and tumor growth arrested after treatment. Conclusion: PDT can be delivered effectively to a lesion in the anterior retina and should be included as an option for treating anteriorly located RCH when conventional cryotherapy and laser photocoagulation fail.